Inhibition of PI3K/Akt/NF‐κB signaling with leonurine for ameliorating the progression of osteoarthritis: In vitro and in vivo studies - Hu, Zhi‐Chao; Gong, Lan‐Fang; Li, Xiao‐Bin; Fu, Xin; Xuan, Jiang‐Wei; Feng, Zhen‐Hua; Ni, Wen‐Fei (Journal of cellular physiology, 2019)
Osteoarthritis (OA) is characterized as the degeneration and destruction of articular cartilage. In recent decades, leonurine (LN), the main active component in medical and edible dual purpose plant Herba Leonuri, has been shown associated with potent anti‐inflammatory effects in several diseases. In the current study, we examined the protective effects of LN in the inhibition of OA development as well as its underlying mechanism both in vitro and in vivo experiments. In vitro, interleukin‐1 beta (IL‐1β) induced over‐production of prostaglandin E2, nitric oxide, inducible nitric oxide synthase, cyclooxygenase‐2, interleukin‐6 and tumor necrosis factor alpha were all inhibited significantly by the pretreatment of LN at a dose‐dependent manner (5, 10, and 20 µM). Moreover, the expression of thrombospondin motifs 5 (ADAMTS5) and metalloproteinase 13 (MMP13) was downregulated by LN. All these changes led to the IL‐1β induced degradation of extracellular matrix. Mechanistically, the LN suppressed IL‐1β induced activation of the PI3K/Akt/NF‐κB signaling pathway cascades. Meanwhile, it was also demonstrated in our molecular docking studies that LN had strong binding abilities to PI3K. In addition, LN was observed exerting protective effects in a surgical induced model of OA. To sum up, this study indicated LN could be applied as a promising therapeutic agent in the treatment of OA. Inhibition of PI3K/Akt/NF‐κB signaling with leonurine for ameliorating the progression of osteoarthritis: in vitro and in vivo studies